Influence of feeding enzymatically hydrolysed yeast cell wall + yeast culture on growth performance of calf-fed Holstein steers - J. Salinas-Chavira; M. F. Montano; N. Torrentera; R. A. Zinn (Journal of Applied Animal Research, 2018)
One hundred and sixty-eight crossbred steers (133 ± 7 kg) were used in a 336-d experiment to evaluate the effects of enzymatically hydrolysed yeast cell wall plus yeast culture (EHY) supplementation on growth performance and carcass characteristics. Treatments consisted of steam-flaked corn-based diet supplemented with 0, 195, 390 or 585 mg/kg EHY. Supplemental EHY enhanced overall (336-d) dry matter intake (DMI, P < .01), averagde daily gain (ADG, P = .04), and final carcass weight (P = .04). Responses were maximal (quadratic effect, P ≤ .02) at the 195 mg/kg level of EHY supplementation. Feed intake enhancements were observed throughout each 112-d period of the study. Improvements in ADG were largely the result of increased DMI, as gain efficiency and estimated dietary net energy (NE) were not affected by EHY supplementation. Effects of supplemental EHY on other carcass measures were not appreciable (P > .20), except for a slight lowering (0.7%, P = .04) in carcass yield. We conclude that throughout the growing-finishing period, supplemental EHY will enhance ADG, resulting in marked increases in final carcass weight. This effect is due to consistent increases in DMI, as supplementation did not affect gain efficiency or estimated dietary NE.